Methodological options for educational escape rooms in university students (Training and Practice : Journal of Educational Sciences, 2022)
One of the main advantages of the educational escape room is the increase of students' motivation to master the curriculum, while the development of soft skills is also essential during the application of this method. In our research, we examine the methodological possibilities of this innovative teaching method among students in higher education. The main question of our research is how the collaborative problem-solving competence can be measured through the escape room, and what characterizes the collaborative problem-solving competence of students of the University of Novi Sad Hungarian language Teacher Training Faculty, in Subotica (Serbia). In our study, relying on existing literature, we describe the methodological possibilities of educational purposes escape rooms. In the paper, we briefly present our educational escape room.
Keywords: collaborative problem-solving competence; escape room; methodological innovation